Remote sensing-based tool to assess nitrogen levels in farmers fields, to support farmers' stover+fertilizer use/management - CGIAR Research Program on Maize (2020)
Initial comparison between ground- and aerial-based tools made. Further multi-location validation required. As low-cost tool in comparison to the more specialized leaf-clip sensors, digital photography is promising approach for precision agriculture crop management. Ground and aerial platform-based measurements performed similarly in terms of assessing leaf N content and GY.